Registo Português de Miocardiopatia Hipertrófica - Cardim, Nuno (2018)
Funding Information: Gold: Jaba Recordati, Merck Serono, Sanofi-Genzyme, Shire; Silver: Medinfar, Servier IOi was supported by the Italian Ministry of Health (“LVH in aortic valve disease and HCM: genetic basis, biophysical correlates and viral therapy models” (RF-2013-02356787), and NET-2011-02347173 (“Mechanisms and treatment of coronary microvascular dysfunction in patients with genetic or secondary LVH”); and by Telethon Italy (GGP13162). Publisher Copyright: © 2017 Sociedade Portuguesa de Cardiologia